High-refractive-index material composition and optical material prepared from composition
By controlling the gel points of cyclic sulfur compounds and polythiol compositions in high refractive index optical resin materials and using program temperature control technology, the problems of high yellow index and edge whitening of the material are solved, and high refractive index and high refractive index are achieved Properties of optical resin material production.
Patent Information
- Application Number
- CN202411482003.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-23
- Publication Date
- 2025-01-03
AI Technical Summary
In the production process of high refractive index optical resin materials, it is difficult for the existing technology to effectively control the gel points of the composition, resulting in bad phenomena such as high yellow index and edge whitening. In addition, there is little investment in research on cyclic sulfur compounds in China, and the production of raw materials is produced by low domestic investment in cyclic sulfur compounds. Monopolized by foreign companies.
By adding 0.01-0.1% catalyst to the cyclic sulfur compound and polythiol composition, the gel point of the composition is defined to be 30-60°C, especially the selection of suitable cyclic sulfur compound and polythiol, and the procedure control is adopted The temperature polymerization curing process controls the gel point at 45-60°C to solve the problem of unevenness in the reaction process.
A high-refractive index optical resin material with low yellow index and no whitening edges is achieved. The refractive index can reach 1.74, higher than the conventional 1.60-1.67, and avoid material texture and other uneven problems, improving the performance and production efficiency of the material. .
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of optical materials, and in particular relates to a high-refractive material composition and an optical material obtained from the composition. Background Art
[0002] Plastic materials have the advantages of light weight, easy processing, high toughness, not easy to break, and easy to dye. In recent years, they have been mostly used as optical materials and are increasingly widely used in the optical lens market.
[0003] Since the beginning of the 21st century, optical resin lenses have been developing towards being safer, lighter and thinner. In particular, the development has been more rapid in recent years. The higher the refractive index of the material, the thinner and lighter the lens. On the premise of ensuring the comprehensive performance of the lens, improving the refractive index of the lens has become the direction of lens development.
[0004] In order to realize high refractive index optical resin materials, episulfide compounds and thiol monomers have become commonly used compositions. However, during the polymerization and curing process, it is easy to cause undesirable phenomena such as high yellow index, many surface textures, and edge whitening. In the technology of high refractive index optical resin materials, domestic research on episulfide compounds and their compositions started late and invested little, especially the production raw materials were monopolized by foreign companies.
[0005] In the patent HK1170753A1, by setting the water content of the polythiol compound and the polyiso(thio)cyanate compound for optical materials to 10 to 300 ppm, a high-performance polyurethane resin optical material without generating white turbidity can be produced well.
[0006] In the patent CN103108918B, inorganic acid treatment is used in the preparation process of the polythiol compound. However, the residual inorganic acid in the composition reduces the activity of the polymerization catalyst when preparing the optical resin, causing a decrease in the reaction rate, leakage and whitening. Therefore, the scheme proposes that this problem can be solved by means of pH adjustment, thereby increasing the viscosity of the polymerization composition, solving the dissolution of the adhesive tape using cheap general isocyanate compounds, the whitening phenomenon at the edge of the optical lens, and the polymerization imbalance problem.
[0007] In the patent CN106715502B, in the process of preparing optical materials, the thiol equivalent of the polythiol compound is measured, and the thiol equivalent ratio relative to the theoretical value of the thiol equivalent is greater than 0.975 and less than 1.000, which can provide a method for producing a polymerizable composition that can suppress the turbidity, optical deformation and streaks of the obtained transparent resin.
[0008] Although the above-mentioned prior arts all record that the problem of white turbidity can be effectively solved, none of them discloses a technical solution related to the gel point of the composition. The present application is a further study in this regard. Summary of the invention
[0009] The inventors have made continuous efforts to study the above-mentioned undesirable phenomena and found that limiting the gel point of the key composition to 30-60°C can solve the problems of low yellow index and no whitening at the edge after curing of the composition. The main raw materials of the composition contain episulfide compounds and polythiol, and the gel point of the composition is specifically limited to 30-60°C.
[0010] The inventors found that the material system of the episulfide compound composition is different from the polyurethane material system. In the episulfide compound composition system, alkaline catalysts are often used to catalyze the ring opening of the episulfide group during curing. However, the heat released by the episulfide group during the ring opening is very large and difficult to control, which makes it difficult to conduct the heat in the mold, resulting in excessively high temperature, causing the episulfide compound to desulfurize and causing the material yellow index to be high. Through the control of the gel point of the episulfide compound and the influence of the reaction process, it is found that the gel point has a very important effect on the performance after curing in the preparation stage of the prepolymer and the cross-linking curing stage. If the gel point is too high, the composition is kept in the low temperature section for a long time during the prepolymerization and curing stage, which is difficult to cure, causing the prepolymer before the gel point to contact the winding tape, dissolve and react, causing the edge whitening problem; if the gel point is too low, the reaction rate of the composition is fast, and the heat release is serious, causing the episulfide compound to desulfurize, resulting in a high yellow index and uneven curing to produce material grains. Finally, the inventors found that the gel point of the composition is specifically limited to 30-60°C, and the reaction process is controllable, which plays a great role in improving the above problems. Further, the gel point can be controlled at 45-60°C. In addition to the influence of the material itself, the amount of catalyst added in the above composition has a great influence on the gel point. The inventors finally found that when the above composition is selected, the catalyst accounting for 0.01-0.1% of the total weight of the episulfide compound and the polythiol is added; the gel point of the composition can be controlled to 30-60°C.
[0011] Based on this, the specific technical solutions of the present invention are as follows: A high-refractive material composition comprises 70-95 parts by weight of an episulfide compound, 5-30 parts by weight of a polythiol and 0.01-0.1% by weight of a catalyst accounting for the total weight of the episulfide compound and the polythiol; and the gel point of the composition is 30-60°C.
[0012] Preferably, the episulfide compound is selected from one or more of bis(β-epithiopropyl)disulfide, bis(β-epithiopropyl)sulfide, bis(β-epithiopropylthio)methane, 1,3-bis(β-epithiopropylthio)cyclohexane, bis(β-epithiopropylthioethyl)sulfide, bis(β-epithiopropyl)trisulfide, 1,2-bis(β-epithiopropylthio)ethane, 1,3-bis(β-epithiopropylthio)propane, 1,3-bis(β-epithiopropylthiomethyl)cyclohexane, 1,4-bis(β-epithiopropylthio)butane, 1,4-bis(β-epithiopropylthio)cyclohexane and 1,4-bis(β-epithiopropylthiomethyl)cyclohexane.
[0013] Preferably, the polythiol is selected from the group consisting of thiodiglycol mercaptan, methanethiol, 1,2-ethanethiol, 1,1-propanethiol, 1,2-propanethiol, 1,3-propanethiol, 2,2-propanethiol, 1,6-hexanethiol, 1,2,3-propanetriol, 1,1-cyclohexanethiol, 1,2-cyclohexanethiol, 2,2-dimethylpropane-1,3-thiol, 3,4-dimethoxybutane-1,2-thiol, 2-dimethylcyclohexane-2,3-thiol, 1,1-bis(mercaptomethyl)cyclohexane, 2,3-dithio(2-thiol)-1-propanethiol, 2,3-dithio-1-propanol (2-thioacetate), 2 ,3-dimercapto-1-propanol (3-mercaptopropionate), diethylene glycol bis(2-mercaptoacetate), diethylene glycol bis(3-mercaptopropionate), 1,2-dimercaptopropyl methyl ether, 2,3-dimercaptopropyl methyl ether, bis(2-mercaptoethyl) ether, ethylene glycol bis(2-mercaptoacetate), ethylene glycol bis(3-mercaptopropionate), trimethylolpropane bis(2-mercaptoacetate), pentaerythritol tetra(2-mercaptoacetate), pentaerythritol tetra(3-mercaptobutyrate), 1,1,2,2-tetrakis(mercaptomethylthio)ethane, 4,8-dimercaptomethyl-1,11-dimercapto-3,6 ,9-trithiaundecane, pentaerythritol tetrakis(3-mercaptopropionate), pentaerythritol tris(3-mercaptopropionate), trimethylolpropane tris(3-mercaptopropionate), 4-mercaptomethyl-1,8-dimercapto-3,6-dithiooctane, tetrakis(mercaptomethyl)methane, 2,5-dimercaptomethyl-1,4-dithiane, one or more of dipentaerythritol hexa(3-mercaptopropionate).
[0014] The catalyst is selected from one or more of tetramethylphosphonium bromide, tetraethylphosphonium chloride, tetraethylphosphonium bromide, tetrabutylphosphonium chloride, tetrabutylphosphonium bromide, tetra-n-butylphosphonium bromide, N,N-dihexylmethylamine and N,N-dimethylcyclohexylamine.
[0015] Furthermore, the episulfide compound is selected from one or more of bis(β-epithiopropyl) disulfide, bis(β-epithiopropyl) sulfide, and bis(β-epithiopropylthio)methane; the polythiol is selected from one or more of pentaerythritol tetrakis(3-mercaptobutyrate), 4,8-dimercaptomethyl-1,11-dimercapto-3,6,9-trithiaundecane, pentaerythritol tetrakis(3-mercaptopropionate), pentaerythritol tris(3-mercaptopropionate), trimethylolpropane tris(3-mercaptopropionate), and 4-mercaptomethyl-1,8-dimercapto-3,6-dithiooctane; and the catalyst is selected from N,N-dihexylmethylamine or N,N-dimethylcyclohexylamine.
[0016] Preferably, the raw materials of the high-refractive material composition further include a release agent accounting for 0.0001-0.01% of the total weight of the episulfide compound and the polythiol; the release agent is selected from one or more of lauryl alcohol polyoxyethylene ether phosphate, dibutyl phosphate, polyoxyethylene ether phosphate, and nonylphenol polyoxyethylene ether phosphate. More preferably, the release agent is selected from lauryl alcohol polyoxyethylene ether phosphate or nonylphenol polyoxyethylene ether phosphate.
[0017] In addition, the inventors also claim to protect an optical material obtained using the above-mentioned high-refractive material composition as a raw material, specifically, the optical material is obtained by subjecting the raw material to programmed temperature-controlled polymerization and curing.
[0018] It is necessary to firstly test the gel point of the prepolymer composed of the high-refractive material composition. Only when the gel point is 30-60°C can the reaction be carried out to avoid various problems of the material after curing.
[0019] The program temperature controlled primary curing process is 15-110℃, curing for 15-30h; the secondary curing process is 100-120℃, curing for 2-4h.
[0020] The optical material obtained above is preferably used in the field of optical lenses.
[0021] Compared with the prior art, the present application strictly controls the gel point of the composition so that the optical resin material obtained by finally curing the composition as a raw material has the characteristics of low yellowness index and no whitening at the edge, and the optical resin material has a higher refractive index, which can reach 1.74, higher than the conventional 1.60-1.67. DETAILED DESCRIPTION
[0022] The technical solution of the present invention is further described below in conjunction with specific embodiments. These embodiments are only used to illustrate the technical solution of the present invention in more detail and should not be construed as limiting the protection scope of the present invention.
[0023] The preparation of the high refractive index material composition and the optical material obtained from the composition in the following embodiments specifically includes the following steps: (1) Prepolymer composition: fully mix the episulfide compound, polythiol, catalyst and release agent at 10°C-20°C, and take samples to measure the properties; (2) Vacuum degassing: The above mixture is subjected to vacuum degassing for 60-90 minutes under stirring conditions; (3) Filtration and casting: The mixture is filtered through a 3 μm polytetrafluoroethylene filter membrane and then cast into a mold with a tape wrapped around the edge; (4) Primary curing: Place the mold in a programmed temperature curing oven and control the temperature at 15-110°C for primary curing for 15-30 hours; (5) Material mold opening: Use a special lens mold opener to open the mold; (6) Edge trimming and cleaning: trim and clean the optical material after mold opening, and observe the results; (7) Secondary curing: The cleaned lenses are placed in a programmed temperature curing oven at 100-120°C for 2-4 hours. After curing, take out the lenses and test their performance.
[0024] The physical properties of the optical materials obtained below were tested according to the following methods: Determination of gel point: Take an appropriate amount of prepolymer composition and put it into a container, and immerse the container in a water bath. Control the temperature of the water bath and the heating rate of the water bath to 3°C / hour. Insert a stirring glass rod into it and start measuring. Use a gelation time tester (GT-III) to monitor the test process until the gel point is reached and record the material temperature.
[0025] Refractive index (ne): The sample was prepared according to the above method, and the data of wavelength 546.1nm (mercury green e-line) was measured at 20°C using Multi-wave length AbbeRefractometer DR-M4 (manufactured by ATTGO Co., Ltd.).
[0026] Yellowness index (YI value): Refer to the method in standard ASTM D:1925 to test performance.
[0027] Edge whitening: The edges of the molded article were irradiated with an ultra-high pressure mercury lamp (light source model OPM-252HEG: manufactured by USHIO Inc.), and the edges were visually observed to see if white fog was generated.
[0028] Example 1 A high refractive index material composition and a method for preparing an optical material from the composition: (1) Preparation of high-refractive material composition: accurately weigh 90 g of bis(β-epithiopropyl) disulfide, 10 g of 4,8-dimercaptomethyl-1,11-dimercapto-3,6,9-trithiaundecane, 0.08 g of N,N-dihexylmethylamine, and 0.005 g of lauryl alcohol polyoxyethylene ether phosphate, mix and dissolve them uniformly at room temperature to obtain a prepolymer liquid; the gel point of the prepolymer liquid was measured, and the result showed that the gel point was 55°C.
[0029] The preparation of optical materials, the specific steps are as follows: (2) Vacuum degassing: The prepolymer liquid is subjected to vacuum degassing for 60 minutes under stirring conditions.
[0030] (3) Filtration and casting: The prepolymer liquid is filtered through a polytetrafluoroethylene filter membrane with a pore size of 3 μm and injected into a mold for preparing the winding tape; (4) Primary curing: Place the mold in a programmed temperature curing oven at 20-110°C for primary curing for 30 hours.
[0031] (5) Material mold opening: Use a special lens mold opener to open the mold.
[0032] (6) Edge trimming and cleaning: The optical material after mold opening is trimmed and cleaned.
[0033] (7) Secondary curing: The cleaned lenses were placed in a programmed temperature curing oven at 110°C for secondary curing for 2 h. After curing, the lenses were taken out and tested for their refractive index, yellowness index and edge whitening. The results are shown in Table 1.
[0034] Example 2 A high refractive index material composition and a method for preparing an optical material from the composition: (1) Preparation of high-refractive material composition: accurately weigh 90 g of bis(β-epithiopropyl) disulfide, 10 g of 4,8-dimercaptomethyl-1,11-dimercapto-3,6,9-trithiaundecane, 0.07 g of N,N-dihexylmethylamine, and 0.005 g of lauryl alcohol polyoxyethylene ether phosphate, mix and dissolve them uniformly at room temperature to obtain a prepolymer liquid; the gel point of the prepolymer liquid was measured, and the result showed that the gel point was 50°C.
[0035] The preparation of optical materials, the specific steps are as follows: (2) Vacuum degassing: The prepolymer liquid is subjected to vacuum degassing for 60 minutes under stirring conditions.
[0036] (3) Filtration and casting: The prepolymer liquid is filtered through a polytetrafluoroethylene filter membrane with a pore size of 3 μm and injected into a mold for preparing the winding tape; (4) Primary curing: Place the mold in a programmed temperature curing oven at 20-110°C for primary curing for 25 hours.
[0037] (5) Material mold opening: Use a special lens mold opener to open the mold.
[0038] (6) Edge trimming and cleaning: The optical material after mold opening is trimmed and cleaned.
[0039] (7) Secondary curing: The cleaned lenses were placed in a programmed temperature curing oven at 110°C for secondary curing for 2 h. After curing, the lenses were taken out and tested for their refractive index, yellowness index and edge whitening. The results are shown in Table 1.
[0040] Example 3 A high refractive index material composition and a method for preparing an optical material from the composition: (1) Preparation of high-refractive material composition: accurately weigh 90 g of bis(β-epithiopropyl) disulfide, 10 g of 4,8-dimercaptomethyl-1,11-dimercapto-3,6,9-trithiaundecane, 0.06 g of N,N-dihexylmethylamine, and 0.005 g of lauryl alcohol polyoxyethylene ether phosphate, mix and dissolve them uniformly at room temperature to obtain a prepolymer liquid; the gel point of the prepolymer liquid was measured, and the result showed that the gel point was 46°C.
[0041] The preparation of optical materials, the specific steps are as follows: (2) Vacuum degassing: The prepolymer liquid is subjected to vacuum degassing for 60 minutes under stirring conditions.
[0042] (3) Filtration and casting: The prepolymer liquid is filtered through a polytetrafluoroethylene filter membrane with a pore size of 3 μm and injected into a mold for preparing the winding tape; (4) Primary curing: Place the mold in a programmed temperature curing oven at 20-110°C for primary curing for 30 hours.
[0043] (5) Material mold opening: Use a special lens mold opener to open the mold.
[0044] (6) Edge trimming and cleaning: The optical material after mold opening is trimmed and cleaned.
[0045] (7) Secondary curing: The cleaned lenses were placed in a programmed temperature curing oven at 110°C for secondary curing for 2 h. After curing, the lenses were taken out and tested for their refractive index, yellowness index and edge whitening. The results are shown in Table 1.
[0046] Example 4 A high refractive index material composition and a method for preparing an optical material from the composition: (1) Prepolymer composition: Accurately weigh 90 g of bis(β-epithiopropyl)sulfide, a cyclic sulfide compound, 10 g of pentaerythritol tetrakis(3-mercaptobutyrate), 0.06 g of N,N-dimethylcyclohexylamine, and 0.00015 g of lauryl alcohol polyoxyethylene ether phosphate, and mix and dissolve them uniformly at room temperature to obtain a prepolymer liquid; the gel point of the prepolymer liquid was measured, and the result showed that the gel point was 42°C.
[0047] The preparation of optical materials, the specific steps are as follows: (2) Vacuum degassing: The prepolymer liquid is subjected to vacuum degassing for 60 minutes under stirring conditions.
[0048] (3) Filtration and casting: The prepolymer liquid is filtered through a polytetrafluoroethylene filter membrane with a pore size of 3 μm and injected into a mold for preparing the winding tape; (4) Primary curing: Place the mold in a programmed temperature curing oven at 20-110°C for primary curing for 30 hours.
[0049] (5) Material mold opening: Use a special lens mold opener to open the mold.
[0050] (6) Edge trimming and cleaning: The optical material after mold opening is trimmed and cleaned.
[0051] (7) Secondary curing: The cleaned lenses were placed in a programmed temperature curing oven at 100°C for 2 h. After curing, the lenses were taken out and tested for refractive index, yellow index and edge whitening. The results are shown in Table 1.
[0052] Example 5 A high refractive index material composition and a method for preparing an optical material from the composition: (1) Prepolymer composition: 80 g of the cyclic sulfide compound bis(β-epithiopropyl) trisulfide, 20 g of tetrakis(mercaptomethyl)methane, 0.07 g of tetramethylphosphonium bromide, and 0.00016 g of nonylphenol polyoxyethylene ether phosphate were accurately weighed, and mixed and dissolved uniformly at room temperature to obtain a prepolymer liquid; the gel point of the prepolymer liquid was measured, and the result showed that the gel point was 38°C.
[0053] The preparation of optical materials, the specific steps are as follows: (2) Vacuum degassing: The prepolymer liquid is subjected to vacuum degassing for 60 minutes under stirring conditions.
[0054] (3) Filtration and casting: The prepolymer liquid is filtered through a polytetrafluoroethylene filter membrane with a pore size of 3 μm and injected into a mold for preparing the winding tape; (4) Primary curing: Place the mold in a programmed temperature curing oven at 20-110°C for primary curing for 30 hours.
[0055] (5) Material mold opening: Use a special lens mold opener to open the mold.
[0056] (6) Edge trimming and cleaning: The optical material after mold opening is trimmed and cleaned.
[0057] (7) Secondary curing: The cleaned lenses were placed in a programmed temperature curing oven at 110°C for secondary curing for 3 h. After curing, the lenses were taken out and tested for their refractive index, yellow index and edge whitening. The results are shown in Table 1.
[0058] Example 6 A high refractive index material composition and a method for preparing an optical material from the composition: (1) Prepolymer composition: Accurately weigh 75 g of the cyclic sulfide compound 1,3-bis(β-epithiopropylthio)cyclohexane, 25 g of dipentaerythritol hexa(3-mercaptopropionic acid), 0.05 g of tetrabutylphosphonium bromide, and 0.0002 g of nonylphenol polyoxyethylene ether phosphate, and mix and dissolve them uniformly at room temperature to obtain a prepolymer liquid; the gel point of the prepolymer liquid was measured, and the result showed that the gel point was 34°C.
[0059] The preparation of optical materials, the specific steps are as follows: (2) Vacuum degassing: The prepolymer liquid is subjected to vacuum degassing for 60 minutes under stirring conditions.
[0060] (3) Filtration and casting: The prepolymer liquid is filtered through a polytetrafluoroethylene filter membrane with a pore size of 3 μm and injected into a mold for preparing the winding tape; (4) Primary curing: Place the mold in a programmed temperature curing oven at 20-110°C for primary curing for 30 hours.
[0061] (5) Material mold opening: Use a special lens mold opener to open the mold.
[0062] (6) Edge trimming and cleaning: The optical material after mold opening is trimmed and cleaned.
[0063] (7) Secondary curing: The cleaned lenses were placed in a programmed temperature curing oven at 120°C for secondary curing for 2 h. After curing, the lenses were taken out and tested for their refractive index, yellow index and edge whitening. The results are shown in Table 1.
[0064] Comparative Example 1 A composition and a method for preparing an optical material from the composition: (1) Prepolymer composition: accurately weigh 90 g of bis(β-epithiopropyl) disulfide, 10 g of 4,8-dimercaptomethyl-1,11-dimercapto-3,6,9-trithiaundecane, 0.15 g of N,N-dihexylmethylamine and 0.005 g of lauryl alcohol polyoxyethylene ether phosphate, mix and dissolve them uniformly at room temperature to obtain a prepolymer liquid; the gel point of the prepolymer liquid was measured, and the result showed that the gel point was 25°C.
[0065] (2) Vacuum degassing: The prepolymer liquid is subjected to vacuum degassing for 60 minutes under stirring conditions.
[0066] (3) Filtration and casting: The prepolymer liquid is filtered through a polytetrafluoroethylene filter membrane with a pore size of 3 μm and injected into a mold for preparing the winding tape; (4) Primary curing: Place the mold in a programmed temperature curing oven at 20-110°C for primary curing for 30 hours.
[0067] (5) Material mold opening: Use a special lens mold opener to open the mold.
[0068] (6) Edge trimming and cleaning: The optical material after mold opening is trimmed and cleaned.
[0069] (7) Secondary curing: The cleaned lenses were placed in a programmed temperature curing oven at 110°C for secondary curing for 2 h. After curing, the lenses were taken out and tested for their refractive index, yellowness index and edge whitening. The results are shown in Table 1.
[0070] Comparative Example 2 A composition and a method for preparing an optical material from the composition: (1) Prepolymer composition: (1) Preparation of high-refractive material composition: Accurately weigh 90 g of bis(β-epithiopropyl) disulfide, 10 g of trimethylolpropane tris(3-mercaptopropionate), 0.13 g of N,N-dihexylmethylamine, and 0.005 g of lauryl alcohol polyoxyethylene ether phosphate, mix and dissolve them uniformly at room temperature to obtain a prepolymer liquid; the gel point of the prepolymer liquid was measured, and the result showed that the gel point was 27°C.
[0071] (2) Vacuum degassing: The prepolymer liquid is subjected to vacuum degassing for 60 minutes under stirring conditions.
[0072] (3) Filtration and casting: The prepolymer liquid is filtered through a polytetrafluoroethylene filter membrane with a pore size of 3 μm and injected into a mold for preparing the winding tape; (4) Primary curing: Place the mold in a programmed temperature curing oven at 20-110°C for primary curing for 30 hours.
[0073] (5) Material mold opening: Use a special lens mold opener to open the mold.
[0074] (6) Edge trimming and cleaning: The optical material after mold opening is trimmed and cleaned.
[0075] (7) Secondary curing: The cleaned lenses were placed in a programmed temperature curing oven at 110°C for secondary curing for 2 h. After curing, the lenses were taken out and tested for their refractive index, yellowness index and edge whitening. The results are shown in Table 1.
[0076] Comparative Example 3 A composition and a method for preparing an optical material from the composition: (1) Prepolymer composition: 90 g of 1,4-bis(β-epithiopropylthio)cyclohexane, 10 g of 2,3-dimercapto-1-propanol (2-thioglycolate), 0.007 g of N,N-dimethylcyclohexylamine and 0.0001 g of lauryl alcohol polyoxyethylene ether phosphate were accurately weighed and mixed and dissolved uniformly at room temperature to obtain a prepolymer liquid. The gel point of the prepolymer liquid was measured, and the result showed that the gel point was 70°C.
[0077] (2) Vacuum degassing: The prepolymer liquid is subjected to vacuum degassing for 60 minutes under stirring conditions.
[0078] (3) Filtration and casting: The prepolymer liquid is filtered through a polytetrafluoroethylene filter membrane with a pore size of 3 μm and injected into a mold for preparing the winding tape; (4) Primary curing: Place the mold in a programmed temperature curing oven at 20-110°C for primary curing for 30 hours.
[0079] (5) Material mold opening: Use a special lens mold opener to open the mold.
[0080] (6) Edge trimming and cleaning: The optical material after mold opening is trimmed and cleaned.
[0081] (7) Secondary curing: The cleaned lenses were placed in a programmed temperature curing oven at 110°C for secondary curing for 2 h. After curing, the lenses were taken out and tested for their refractive index, yellowness index and edge whitening. The results are shown in Table 1.
[0082] Comparative Example 4 A composition and a method for preparing an optical material from the composition: (1) Prepolymer composition: Accurately weigh 90 g of the cyclic sulfide compound bis(β-epithiopropyl) disulfide, 10 g of 4,8-dimercaptomethyl-1,11-dimercapto-3,6,9-trithiaundecane, 0.004 g of N,N-dimethylcyclohexylamine, and 0.0001 g of lauryl alcohol polyoxyethylene ether phosphate, and mix and dissolve them uniformly at room temperature to obtain a prepolymer liquid; the gel point of the prepolymer liquid was measured, and the result showed that the gel point was 75°C.
[0083] (2) Vacuum degassing: The prepolymer liquid is subjected to vacuum degassing for 60 minutes under stirring conditions.
[0084] (3) Filtration and casting: The prepolymer liquid is filtered through a polytetrafluoroethylene filter membrane with a pore size of 3 μm and injected into a mold for preparing the winding tape; (4) Primary curing: Place the mold in a programmed temperature curing oven at 20-110°C for primary curing for 30 hours.
[0085] (5) Material mold opening: Use a special lens mold opener to open the mold.
[0086] (6) Edge trimming and cleaning: The optical material after mold opening is trimmed and cleaned.
[0087] (7) Secondary curing: The cleaned lenses were placed in a programmed temperature curing oven at 110°C for secondary curing for 2 h. After curing, the lenses were taken out and tested for their refractive index, yellowness index and edge whitening. The results are shown in Table 1.
[0088] The various physical properties of the optical resins obtained in Examples 1-6 and Comparative Examples 1-4 are specifically listed in Table 1: Table 1 Test performance of Examples 1-6 and Comparative Examples 1-4 Example Refractive index Ne Yellow Index YI Edge Whitening Example 1 1.738 3.26 none Example 2 1.738 3.35 none Example 3 1.738 3.47 none Example 4 1.736 3.63 none Example 5 1.735 4.01 none Example 6 1.721 4.12 none Comparative Example 1 1.736 7.57 have Comparative Example 2 1.735 8.21 have Comparative Example 3 1.739 6.24 none Comparative Example 4 1.740 8.91 none From the data in Table 1, it can be clearly seen that the yellowness index of the optical resin material in Examples 1-6 is significantly lower than that in Comparative Examples 1-4, and edge whitening is obvious when the gel point is low, which effectively proves that the composition of the present invention has obvious advantages in controlling the gel point at 30-60° C., and a defect-free, high-refractive-index resin material with a high pass rate is obtained. The preparation of the resin material by the present invention has made significant progress in the composition containing episulfide compounds, and has the significance and value of industrial production and application.
[0089] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any equivalent substitutions, modifications, etc. made by technicians in this field without any creative work within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A high-refractive material composition, characterized in that: The raw materials of the composition contain 70-95 parts of an episulfide compound, 5-30 parts of polythiol and 0.01-0.1% of a catalyst accounting for the total weight of the episulfide compound and the polythiol by weight; and the gel point of the composition is 30-60°C.
2. The high-refractive material composition according to claim 1, characterized in that: The episulfide compound is selected from one or more of bis(β-epithiopropyl)disulfide, bis(β-epithiopropyl)sulfide, bis(β-epithiopropylthio)methane, 1,3-bis(β-epithiopropylthio)cyclohexane, bis(β-epithiopropylthioethyl)sulfide, bis(β-epithiopropyl)trisulfide, 1,2-bis(β-epithiopropylthio)ethane, 1,3-bis(β-epithiopropylthio)propane, 1,3-bis(β-epithiopropylthiomethyl)cyclohexane, 1,4-bis(β-epithiopropylthio)butane, 1,4-bis(β-epithiopropylthio)cyclohexane and 1,4-bis(β-epithiopropylthiomethyl)cyclohexane.
3. The high-refractive material composition according to claim 1, characterized in that: The polythiol is selected from the group consisting of thiodiglycol mercaptan, methanethiol, 1,2-ethanethiol, 1,1-propanethiol, 1,2-propanethiol, 1,3-propanethiol, 2,2-propanethiol, 1,6-hexanethiol, 1,2,3-propanetriol, 1,1-cyclohexanethiol, 1,2-cyclohexanethiol, 2,2-dimethylpropane-1,3-thiol, 3,4-dimethoxybutane-1,2-thiol, 2-dimethylcyclohexane-2,3-thiol, 1,1-bis(mercaptomethyl)cyclohexane, 2,3-dithio(2-thiol)-1-propanethiol, 2,3-dithio-1-propanol (2-thioacetate), 2 ,3-dimercapto-1-propanol (3-mercaptopropionate), diethylene glycol bis(2-mercaptoacetate), diethylene glycol bis(3-mercaptopropionate), 1,2-dimercaptopropyl methyl ether, 2,3-dimercaptopropyl methyl ether, bis(2-mercaptoethyl) ether, ethylene glycol bis(2-mercaptoacetate), ethylene glycol bis(3-mercaptopropionate), trimethylolpropane bis(2-mercaptoacetate), pentaerythritol tetra(2-mercaptoacetate), pentaerythritol tetra(3-mercaptobutyrate), 1,1,2,2-tetrakis(mercaptomethylthio)ethane, 4,8-dimercaptomethyl-1,11-dimercapto-3,6 ,9-trithiaundecane, pentaerythritol tetrakis(3-mercaptopropionate), pentaerythritol tris(3-mercaptopropionate), trimethylolpropane tris(3-mercaptopropionate), 4-mercaptomethyl-1,8-dimercapto-3,6-dithiooctane, tetrakis(mercaptomethyl)methane, 2,5-dimercaptomethyl-1,4-dithiane, one or more of dipentaerythritol hexa(3-mercaptopropionate).
4. The high-refractive material composition according to claim 1, characterized in that: The catalyst is selected from one or more of tetramethylphosphonium bromide, tetraethylphosphonium chloride, tetraethylphosphonium bromide, tetrabutylphosphonium chloride, tetrabutylphosphonium bromide, tetra-n-butylphosphonium bromide, N,N-dihexylmethylamine and N,N-dimethylcyclohexylamine.
5. The high-refractive material composition according to any one of claims 1 to 4, characterized in that: The episulfide compound is selected from one or more of bis(β-epithiopropyl) disulfide, bis(β-epithiopropyl) sulfide, and bis(β-epithiopropylthio)methane; the polythiol is selected from one or more of pentaerythritol tetrakis(3-mercaptobutyrate), 4,8-dimercaptomethyl-1,11-dimercapto-3,6,9-trithiaundecane, pentaerythritol tetrakis(3-mercaptopropionate), pentaerythritol tris(3-mercaptopropionate), trimethylolpropane tris(3-mercaptopropionate), and 4-mercaptomethyl-1,8-dimercapto-3,6-dithiooctane; the catalyst is selected from N,N-dihexylmethylamine or N,N-dimethylcyclohexylamine.
6. The high-refractive material composition according to claim 1, characterized in that: The raw materials also include a release agent accounting for 0.0001-0.01% of the total weight of the episulfide compound and the polythiol.
7. The high-refractive material composition according to claim 6, characterized in that: The release agent is selected from one or more of lauryl alcohol polyoxyethylene ether phosphate, dibutyl phosphate, polyoxyethylene ether phosphate, and nonylphenol polyoxyethylene ether phosphate.
8. An optical material obtained by using the high refractive index material composition according to any one of claims 1 to 6 as a raw material, characterized in that: The raw materials are polymerized and cured through programmed temperature control to obtain optical materials.
9. The optical material according to claim 8, characterized in that: The primary process of program temperature control is 15-110℃, and the curing time is 15-30h; the secondary curing process is 100-120℃, and the curing time is 2-4h.
